Peningkatkan Pengetahuan Ibu Tunanetra tentang Kesehatan Kehamilan melalui Buku Suluh Bina Netra Sehat Reproduksi Berhuruf Braille: The Improvement of Knowledge of Blind Mothers about Health in Pregnancy through Counseling using the Book “Suluh Bina Netra Sehat Reproduksi” - Dian Furwasyih; Ilham Akerda Edyyul; Sunesni Sunesni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Blind women often experience discrimination in obtaining public services, such as securing access to health services. Most healthcare facilities they visit during pregnancy do not have information media they can read at home, such as the MCH book for pregnant women who do not have vision problems. In 2020, the service team developed reproductive health education media for blind mothers in Braille. Therefore, the solution we offer to partners is to provide health education using the book Suluh Bina Netra Healthy Reproductive Braille, which we have developed to increase mothers' knowledge about pregnancy check-ups. The methods used in this community service include the lecture method, question and answer, and discussion and practice. The aim is to provide health education to increase the understanding of blind women. The activity was carried out from July 31 to August 15, 2021, with 14 blind mothers. There was an increase in the score on the post-test after the client was given education about pregnancy checks using books, from an average of 3.14 to 5.43. Blind mothers were also satisfied with the activities carried out with an average score for material quality, namely 4.78, media 4.64, and activity benefits 4.78. The output of this activity is an increase in client knowledge after receiving education: the average post-test score increases, the intellectual property rights registration number EC00202185546 on October 14, 2021, and this book has also been launched directly by the Mayor of Padang on December 2, 2021, with a news link https://m.facebook.com/story.php?story_fbid=270755855084449&id=100064501097230&sfnsn=wiwspwa